Efficient Biosynthesis of (R)‐ or (S)‐2‐Hydroxybutyrate from l‐Threonine through a Synthetic Biology Approach. Issue 18 (25th August 2016) - Yao, Peiyuan; Cui, Yunfeng; Yu, Shanshan; Du, Yuncheng; Feng, Jinhui; Wu, Qiaqing; Zhu, Dunming
Abstract: An efficient multi‐enzyme cascade reaction for the synthesis of ( R )‐ or ( S )‐2‐hydroxybutyric acid [( R )‐ or ( S )‐2‐HB] froml ‐threonine was developed by using recombinant Escherichia coli cells expressing separately or co‐expressingl ‐threonine deaminase from Escherichia coli K‐12 ( ilvA ), formate dehydrogenase (FDH) from Candida boidinii andl ‐lactate dehydrogenase (l ‐LDH) from Oryctolagus cuniculus ord ‐lactate dehydrogenase (d ‐LDH) from Staphylococcus epidermidis ATCC 12228. Up to 750 mM ofl ‐threonine were completely transformed to ( R )‐ or ( S )‐2‐HB in optically pure form (>99% ee ) with high isolated yields. This one‐pot multi‐enzyme transformation provides a new practical method for the synthesis of these important optically pure compounds. Abstract :